THE EFFECT OF COMPENSATION AND WORK ENVIRONMENT ON EMPLOYEE WORK SATISFACTION IN. INDOMARCO ADI PRIMA OKU BRANCH EAST - Prihrti, Dimas Veronica; Saputri, Fenty Ayu (Jurnal Manajemen, 2019)
The Influence of Compensation and Work Environment on Employees’ Work Satisfaction at PT. Indomarco Adi Prima, OKU Timur Branch. This study aims to determine the influence of compensation and work environment on employees’ work satisfaction at PT. Indomarco Adi Prima, OKU Timur Branch. The data used is primary data through questionnaires. The population in this study was 34 employees of PT. Indomarco Adi Prima, OKU Timur Branch. The analytical tool used is multiple linear regression, t test, F test, and analysis of the coefficient of determination. From the results of the data analysis results partially obtained that compensation has a significant influence on work Satisfaction with t-count 4.382> t-table 2.039, and the work environment has a significant influence on work Satisfaction with t-count 4.182> t-table 2.039. While simultaneous analysis obtained F count 23,596> F table 3.30, which means that compensation and work environment have a positive and significant influence together on work satisfaction. The magnitude of the coefficient of determination (R2) of the compensation variable and work environment together influence work satisfaction by 60.4% while the remaining 39.6% is influenced or varied by other variables such as leadership, work discipline and motivation.